2014
DOI: 10.7287/peerj.preprints.369v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Women are underrepresented on editorial boards

Abstract: Despite women earning similar numbers of graduate degrees as men in STEM disciplines, they are underrepresented in upper level positions in both academia and industry. Editorial board memberships are an important example of such positions; membership is both a professional honor in recognition of achievement and an opportunity for professional advancement. We surveyed 10 highly regarded journals in environmental biology, natural resource management, and plant sciences to quantify the number of women on their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Hence, the present article aims to create awareness within the editorial sector. Following the good practices advised by Elsevier (2021), editorials are encouraged to include gender information in their web pages, to be able to monitor the policy that most journals want to apply (Cho et al, 2014). But several journals remain still in the very low side of gender balance and transparency in the editorial board composition, including Elsevier's journals (e.g., Journal of Building Engineering, as described above, or Earth and Planetary Sciences, as published by Witze, 2016) as can be seen in the figures above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the present article aims to create awareness within the editorial sector. Following the good practices advised by Elsevier (2021), editorials are encouraged to include gender information in their web pages, to be able to monitor the policy that most journals want to apply (Cho et al, 2014). But several journals remain still in the very low side of gender balance and transparency in the editorial board composition, including Elsevier's journals (e.g., Journal of Building Engineering, as described above, or Earth and Planetary Sciences, as published by Witze, 2016) as can be seen in the figures above.…”
Section: Discussionmentioning
confidence: 99%
“…A wide number of publications conclude that, even if women and men have a similar number of graduate degrees, women remain underrepresented in upper-level positions in all sectors (Cho et al, 2014). Unconscious biases against women have been found in hiring, promotion, publications, citing, and journal placements.…”
Section: Discussionmentioning
confidence: 99%
“…A deeper analysis by subfield reveals further variations with a median of 7.3% editorships held by women among publishers (SIAM publications being the highest-19.1%); and 7.3% editorships held by women among countries with high editorial strength (Canada (12.2%), France (11.7%), Australia (11.4%), and Italy (11.1%) have the greatest representation of women) [61]. A similar study carried out with data from 1985 to 2013, focusing on plant sciences, natural resource management, and environmental biology (10 highly regarded journals in these areas) showed that only 16% of subject editors were women [62]. Recent studies focusing on women from varying geographical regions and income groups of the country of affiliation for editorial leadership positions across 113 rehabilitation and sports science journals revealed that 24.7% were women (1792 out of 7248 editors (35.7% leadership and 64.3% advisors).…”
Section: Need For Diversity At the Top: Highlighting The Need For Edi...mentioning
confidence: 99%